(untitled) (Journal of National Institute of Neurosciences Bangladesh, 2019)
Colchicine is a classical alkaloid drug extracted from plants of the genus Colchicum. Colchicine is very rarely seen as a cause of hypoglycemia. Here we reported a 65 years old female that presented with erythema nodusum, and developed hypoglycemia after being treated with Colchicine. Journal of National Institute of Neurosciences Bangladesh, 2019;5(1): 87-89